A Standardized Diagnostic Pathway for Suspected Appendicitis in Children Reduces Unnecessary Imaging. Issue 2 (March 2022) - D'Cruz, Roshan J.; Linden, Allison F.; Devin, Courtney L.; Savage, Jillian; Zomorrodi, Arezoo; Reichard, Kirk W.; Choudhary, Arabinda; Berman, Loren
Abstract : Introduction: Ultrasound (US) for the diagnosis of acute appendicitis is often nondiagnostic, and additional imaging is required. A standardized approach may reduce unnecessary imaging. Methods: We retrospectively analyzed all patients who had imaging for appendicitis in our emergency department in 2017 and evaluated patient characteristics associated with nondiagnostic US. Using these results, we developed a pediatric appendicitis score (PAS)-based imaging pathway and compared imaging trends prepathway and postpathway implementation. Results: A total of 971 patients received imaging for suspected appendicitis prepathway in 2017. Female sex, obesity, and low/intermediate PAS were significantly associated with nondiagnostic US, but not magnetic resonance imaging (MRI) ( P < 0.0001). Nearly one-third of patients received multiple imaging studies (US followed by MRI/computed tomography). As low/intermediate PAS was most strongly associated with a nondiagnostic US on multivariate analysis, we developed a PAS-based imaging stewardship pathway to eliminate imaging in low-PAS patients and reduce the number of patients with an intermediate PAS who received multiple imaging studies by obtaining an MRI as the first-line study. After implementation, only 22 low-PAS patients received imaging (compared with 238 preimplementation), and the proportion of intermediate-PAS patients receiving multiple imaging studies decreased from 31.4% to 13% ( P < 0.0001). The cost of imaging per 100 patients increased from $24, 255 to $31, 082. Conclusion: A PAS-based imaging stewardship pathway reduces unnecessary imaging for suspected appendicitis.